ANALISIS AKTUALISASI DIRI IPSSAK DALAM FILM âMADANGEUL NAON AMTHAKâ: KAJIAN PSIKOLOGI HUMANISTIK ABRAHAM MASLOW - , ANTIN IRSANTI, Yuni Wachid Asrori, S.S, M.A ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research examines the struggle of Ipssakâs life to figure out what she wants in the film âMadangeul Naon Amthak (Leafie, A Hen Into The Wild)â. Ipssak is a hen that used to live in the chicken farm. Although the chicken farm is her original habitat, Ipssak prefer to live in the nature than in the chicken farm. Eventhough living in the nature are difficult and danger, Ipssak wonât give up easily and keep fighting to survive in the nature. This research uses theory of Abraham Maslow's self-actualization. In addition, this research also uses the theory of self-concept as a supporting factor to achieve the self-actualization of Ipssak. The results of this research indicates that Ipssak can actualize herself by fulfilled the four basic needs of Abraham Maslow's theory which are physiological needs, safety needs, belongingness and love needs, and self-esteem needs. Ipssak also has the characteristics of self-actualizing person as she can see life clearly, devotes herself to her work or duties, has spontaneity and creativity, has low self conflict, has psychological independence, and simply enjoys life and practical in all aspects. Ipssak also has three out of four characteristics of a positive self-concept which are having a confidence to solve a problem, feeling equal to others and accepting praise without feeling embarrassed. Ipssak doesnât have a negative selfconcept, so it makes her easier to reach self-actualization. The self-actualization which can be achieved by Ipssak is that she can survive in the nature with her physical limitations. She can manage to be responsible for herself, capable of being a good mother for her son and she can help another.